Gestión ambiental: una mirada desde la contabilidad (2016)
This article discusses the need for organizations and society that the former have adequate environmental management, based on information provided by accounting. To do so an overview is made through some models of environmental management and assessment, in order to demonstrate the environmental implications of the actions of a company.